The end game: Mortality outcomes in North American professional athletes - Lemez, S.; Wattie, N.; Baker, J. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Comprehensive investigations into the mortality outcomes of elite athletes can assist in decoding risk factors of premature mortality and provide avenues for exploring human health through engagement in sport. As such, the purpose of this study was to comprehensively examine lifespan trends of athletes from the four major sports in North America: Major League Baseball (MLB), National Basketball Association (NBA), National Football League (NFL) and National Hockey League (NHL). We hypothesized that proportional death rates would be similar across the four sports, when standardizing the data by debut years. Overall, 17,523 out of 50,515 (34.7%) athletes were deceased as of the respective data collection cut-off date for their sport, with MLB players having the highest risk of imminent mortality. Professional basketball players generally had the highest relative proportion of death when standardizing data by debut year, although NHL and NFL players who debuted after 2005 had the highest proportion of death. In addition, a one year increase in career length significantly decreased the risk of death (HR .982, 95% CI: .978 - .985), even after adjusting for sport type (HR .977, 95% CI: .974 - .980). Meaningful significance should be considered given the historical and unique nature of the sample. Nevertheless, investigating risk of death differences through different occupational and biological variables can help highlight aversive trends to lifespan that permeate throughout high performance athlete populations.